PERAN MUSIK EREEKNG DALAM RITUAL BELIATN KENYONG SUKU DAYAK TONYOOI - Yogi Kandola; Santosa Soewarlan (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2022)
This study reveals the role of ereekng music in the ritual of Beliatn Kenyong of the Dayak Tonyooi community in Kutai Barat Regency, Kalimantan Timur. The problem that will be described in this paper is to question the role of ereekng music in implementing the ritual ceremony of Beliatn Kenyong. In answering these problems, this study uses an ethnomusicological approach that is supported by theories and concepts of the role of music in traditional community culture. This qualitative research uses interviews, observation, documentation, and literature studies.This study concludes that the cultural customs of the Tonyooi people generally indicate how the balance of the relationship between humans, nature, and God must always be maintained. If the relationship becomes unbalanced, where one of the people violates customary rules, there will be an impact; namely, that person will experience illness. Through the illness that the person feels, the Beliatn Kenyong ritual and all its accessories, including ereekng music, will be carried out. In general, the Beliatn Kenyong ritual is also a sign of the importance of maintaining the balance of the relationship between humans, nature, and God, and specifically, the process of carrying out the concept of balance is symbolized in the presentation of ereekng music and its very significant role in the implementation of the Beliatn Kenyong ritual.